(3GdJQHjI Ydi Gdbje aj GdJYdje GdCSGSj aj dHfGf (B: (3fehPL eOGQS eMGaXI LHd dHfGfs - (3YHO Gddg, eMehO jhSas ((3HjQhJs (3GdLGeYI GddHfGfjI (B- (3GdeYgO GdYGdj ddOcJhQGg aj GdBOGH hGdYdhe GdEfSGfjI GdELJeGYjIs, 2009)
(3JgOa GdOQGSI Edi GdJQcjR Ydi EOGQI hJNWjW GdYedjI GdJQHhjI GdYdejI heaQOGJgG (B((3GdCgOGa, GdcaGjGJ, GdWQGFb, egGQGJ GdLgGR GdJYdjej GdJQHhj, GdESJQGJjLjGJ, GdJbfjGJ, hGdLOhdI GdRefjI ddCfTWI GdeJeMhQI Mhd Gdbje(B). (3HGdEVGaI Edi GSJbUGA eOi JhGaQ gPG GdJNWjW aj GdEOGQI GdeOQSjI, hCfhGY Gdbje GdJj jQZH GdCgd hEOGQI GdeOQSI aj fbdgG ddLjd GdLOjO(B. (3EYJeOJ GdOQGSI GdefgL GdhUaj, hGSJNOeJ JbfjI GdebGHdI GdeaJhMI eY eOjQj GdeOGQS hChdjGA CehQ HYV GdWdGH, HGdEVGaI dJbfjI GdGSJeGQI(B. (3TedJ GdYjfI (B20 (3eOQSI ef GdJYdje GdQSej hGdNGU, ehRYI Hjf ESdGejI heSjMjI, heOQGFgG GdYTQjf, hEbJUQ eLJeY GdOQGSI Ydi eMGaXI LHd dHfGf(B. (3HjfJ GdfJGFL Cf ZGdHjI GdeDSSGJ GdeOQSjI dG JYJeO Ydi efXheI CgOGa hcaGjGJ bjejI eeG jTcd NddG aj JWHjb GdYedjI GdJQHhjI(B. (3cPdc JHjf Cf gPg GdefXheI ZjQ eYeeI CheJHfGI dOi GdLgGR GdJQHhj, adG JJhGaQ HQGeL hefGgL hcJH eYJeOI dZQS Gdbje Vef LOhdI RefjI Ch JhRjY Sfhj ddOQhS Ch GdCfTWI GdcajdI Hfbd Gdbje Vef LOhdI Edi GdCLjGd GdfGTFI, haj MGd hLhOgG aj HYV GdeOGQS dG jNUU dgG GdhbJ GdjSjQ(B. (3jdGMX Cf bdI ef GdeOGQS JOQH GdeYdejf Ydi eaGgje heYGQa Mhd Gdbje hGdegGQGJ GddGReI dJMVjQ GdOQhS hGdCfTWI GdJQHhjI aVdG Yf GdWQGFb GdcajdI HRQY Gdbje, hbdI efge JYJeO dLGfG heTQajf JQYi hJOQH hJQGbH YedjI GdJQHjI Ydi Gdbje(B. (3HGdEVGaI Edi hLhO JhGab Hjf Gdbje GdeQZhHI YfO GdCgd eY Gdbje GdeQZhHI YfO EOGQI GdeOQSI GdQSejI GdJj dG JJHfi JhLkgG OjfkqjG, HGdebGHd dhMX JhGab eJhSW Edi VYja dOi GdeOGQS GdESdGejI hGdeSjMjI(B.s
(3GdfhY (B: (3QSGdIs
Keywords: (3GdJYdje hGdbjes; Basic Education; Curricula; Curriculum; Enseignement de base; Mont Liban; Mount of Lebanon; Valeurs et Education; Values and Education; (3GdJYdje GdCSGSjs; (3GdefGgLs; (3LHd dHfGfs